The cell cycle inhibitor P21 promotes the development of pulmonary fibrosis by suppressing lung alveolar regeneration - Xiaoxi Lv; Chang Liu; Shanshan Liu; Yunxuan Li; Wanyu Wang; Ke Li; Fang Hua; Bing Cui; Xiaowei Zhang; Jiaojiao Yu; Jinmei Yu; ZhuoWei Hu (Elsevier, 2022)
The cell cycle inhibitor P21 has been implicated in cell senescence and plays an important role in the injury-repair process following lung injury. Pulmonary fibrosis (PF) is a fibrotic lung disorder characterized by cell senescence in lung alveolar epithelial cells. In this study, we report that P21 expression was increased in alveolar epithelial type 2 cells (AEC2s) in a time-dependent manner following multiple bleomycin-induced PF. Repeated injury of AEC2s resulted in telomere shortening and triggered P21-dependent cell senescence. AEC2s with elevated expression of P21 lost their self-renewal and differentiation abilities. In particular, elevated P21 not only induced cell cycle arrest in AEC2s but also bound to P300 and β-catenin and inhibited AEC2 differentiation by disturbing the P300-β-catenin interaction. Meanwhile, senescent AEC2s triggered myofibroblast activation by releasing profibrotic cytokines. Knockdown of P21 restored AEC2-mediated lung alveolar regeneration in mice with chronic PF. The results of our study reveal a mechanism of P21-mediated lung regeneration failure during PF development, which suggests a potential strategy for the treatment of fibrotic lung diseases.